2015
DOI: 10.1371/journal.ppat.1004780
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Suppression of HBV RNA through AID-Dependent Recruitment of an RNA Exosome Complex

Abstract: Transforming growth factor (TGF)-β inhibits hepatitis B virus (HBV) replication although the intracellular effectors involved are not determined. Here, we report that reduction of HBV transcripts by TGF-β is dependent on AID expression, which significantly decreases both HBV transcripts and viral DNA, resulting in inhibition of viral replication. Immunoprecipitation reveals that AID physically associates with viral P protein that binds to specific virus RNA sequence called epsilon. AID also binds to an RNA deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 44 publications
2
60
0
Order By: Relevance
“…4 5 2731 The expression of human genes was generally very low or under the detection limit, while the murine counterparts were easily detectable; however, neither murine nor human gene expression was specifically enhanced during the strong proliferation phase (between days 3 and 30) in comparison to values obtained at day 100 (see online supplementary figure S3). These results were also confirmed on the protein level using a magnetic Luminex screening assay for the human analytes tumour necrosis factor, interferon (IFN)B, IFNG, interleukin (IL)28A, IL28B, IL18, IL1B, IL6, epidermal growth factor and hepatocyte growth factor (data not shown), thus suggesting that these factors did not contribute substantially to the drop of cccDNA levels provoked by cell proliferation in this immunodeficient mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…4 5 2731 The expression of human genes was generally very low or under the detection limit, while the murine counterparts were easily detectable; however, neither murine nor human gene expression was specifically enhanced during the strong proliferation phase (between days 3 and 30) in comparison to values obtained at day 100 (see online supplementary figure S3). These results were also confirmed on the protein level using a magnetic Luminex screening assay for the human analytes tumour necrosis factor, interferon (IFN)B, IFNG, interleukin (IL)28A, IL28B, IL18, IL1B, IL6, epidermal growth factor and hepatocyte growth factor (data not shown), thus suggesting that these factors did not contribute substantially to the drop of cccDNA levels provoked by cell proliferation in this immunodeficient mouse model.…”
Section: Resultsmentioning
confidence: 99%
“…This may be part of a larger spectrum of exosomal cofactors activated during infection. The antiviral RNA-binding proteins DDX17, DDX60, ZAP, and AID have all been found to coimmunoprecipitate with the exosome (Guo et al 2007;Lubas et al 2011;Miyashita et al 2011;Moy et al 2014a;Liang et al 2015). Furthermore, both ZAP and AID restrict viral infection only if the exosome is intact.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the human Ski component hSKIV2L has been shown to regulate endogenous RIG-I RNA targets to prevent autoimmunity; however, it likely does so independently of the canonical Ski complex and the exosome (Eckard et al 2014). Additionally, other mammalian antiviral RNA-binding proteins (ZAP, DDX60, and AID) have been shown to bind the exosome and, in some cases, depend on the exosome for their antiviral function; however, none of these factors has been shown to induce exosome-mediated degradation of viral RNAs (Guo et al 2007;Miyashita et al 2011;Liang et al 2015). Furthermore, no studies have explored potential roles of the nuclear exosome cofactors in viral infection.…”
mentioning
confidence: 99%
“…Because of this shuttling property, exosomes take part in many physiological or pathological processes, including intracellular communication, modulation of immune responses, and tumorigenesis [22][23][24]. Reports have also shown that exosomes could shuttle both infectious cargo and protective host molecules between cells [25][26][27][28][29][30][31], but the research of their roles in pathogen infection is still in an early stage. MSCs can produce a high amount of exosomes (MSC-Exo) compared with other cell types [32], and MSC-Exo exert an influence on various diseases similar to that of MSCs [17].…”
Section: Introductionmentioning
confidence: 99%